Naturalizing inequality : water, race, and biopolitics in South Africa - Marcatelli, Michela, 1982- (Critical green engagements., 2021)
"The book discusses the reproduction and legitimization of racial inequality in post-apartheid South Africa. Michela Marcatelli unravels this inequality paradox through an ethnography of water in a rural region of the country. She documents how calls to save nature have only deepened and naturalized inequality"--